Board of Editor - Journal of Infrastructure & Facility Asset Management (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
Board of Editor PATRON : Dean - Faculty of Civil, Environmental, Earth Sciences - ITS. Head Training Center Management & Functional Position - Ministry of PWPH. RESPONSIBLE : Head of Department – Civil Engineering Department - ITSBOARD OF EDITOR Chief Editor : Ria Asih Aryani Soemitro ITS, Indonesia h-index (GS = 10)Founding Editor : Hitapriya Suprayitno ITS, Indonesia h-index (GS = 9) Managing Editor : Trihanyndio Rendy Satrya ITS, Indonesia h-index (GS = 2) Mahendra Andiek Maulana ITS, Indonesia h-index (GS = 2)Editor : Data Iranata ITS, Indonesia h-index (GS =3) Alex Abdi Chalik PUPR, Indonesia h-index (GS = -) Danang Parikesit UGM, Indonesia h-index (GS = 8) Achmad Wicaksono UB, Indonesia h-index (GS= 9) Maimunah Sapri UTM, Malaysia h-index (GS = 16) Wahyu Caesarendra UBS, Brunei Dar es Salam h-index (GS = 19) Address : Editor JIFAM – Room J - 201 Departement of Civil Engineering Institut Teknologi Sepuluh Nopember ITS Campus, Sukolilo, Surabaya 60111 Email : jurnal.jifam@gmail.com Website: https://iptek.its.ac.id/index.php/jifam Reviewer for this EditionRia Asih Aryani Soemitro, Insitut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia.Hitapriya Suprayitno, Insitut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia.Mahendra Andik Maulana, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia.Trihanyndio Rendy Satrya, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, IndonesiaJanuarti Jaya Eka Putri, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia.Akhmad Wicaksono, Universitas Brawijaya (UB), Malang, Indonesia.